TEMPORAL FASCIAL AND APONEUROTIC FLAP FOR TREATMENT OF THE RETROMOLAR AREA CANCER - D. V. Sikorskiy; S. O. Podvyaznikov; A. N. Volodin (Опухоли головы и шеи, 2015)
The article represents a detailed technique of hiding mucosa defects in the retromolar area with temporal fascial and aponeurotic flap as applied to the surgical stage in the combined and complex treatment.